2018
DOI: 10.1111/iwj.12994
|View full text |Cite
|
Sign up to set email alerts
|

Pressure ulcers in cardiac surgery: Few clinical studies, difficult risk assessment, and profound clinical implications

Abstract: Pressure ulcers (PUs) are a common complication after cardiac surgery, with almost one third of patients suffering from PUs during hospitalisation. Because of the burden that PUs exert on both the patients and the health care system, prevention is of utmost importance. The first step in successful prevention, however, includes the identification of the main features that render patients prone to PU development. Cardiac surgery population is not adequately addressed in current clinical trials and studies. Few s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
1
20
1
3
Order By: Relevance
“…This hospital was selected because it has an admission-discharge information management system and optimum level of data documentation in medical files. Moreover, previous studies showed that PUs are a common complication after cardiac surgeries, with a reported incidence range of 30% during hospitalization (Feuchtinger et al, 2005;Chello et al, 2019). The present study found that 21 cases developed PSI03 out of 310 cases who had the inclusion criteria of PSI03 and the incidence risk was 67.7 per 1,000 discharges (95% CI, 44.7-101.3).…”
Section: Patient Safety Indicator 03supporting
confidence: 50%
See 1 more Smart Citation
“…This hospital was selected because it has an admission-discharge information management system and optimum level of data documentation in medical files. Moreover, previous studies showed that PUs are a common complication after cardiac surgeries, with a reported incidence range of 30% during hospitalization (Feuchtinger et al, 2005;Chello et al, 2019). The present study found that 21 cases developed PSI03 out of 310 cases who had the inclusion criteria of PSI03 and the incidence risk was 67.7 per 1,000 discharges (95% CI, 44.7-101.3).…”
Section: Patient Safety Indicator 03supporting
confidence: 50%
“…Another study showed that post-operative PU rate in cardiopulmonary patients was 111/1,000 discharges (40 out of 360 patients) (Campanili et al, 2015). The high incidence rate in the patients who had undergone cardiac surgeries was due to many causes that were explored in previous studies such as Chello et al (2019).…”
Section: Patient Safety Indicator 03mentioning
confidence: 99%
“…In a study of patients undergoing urologic procedures, duration of anesthesia and a diastolic blood pressure of less than 50 mm Hg were predictive of HAPI development, indicating that perfusion during surgery may influence HAPI risk. 33,34 Research is urgently needed to identify intraoperative risk…”
Section: Discussionmentioning
confidence: 99%
“…e133 factors in surgical critical care patients 33 and to identify potentially modifiable risk factors.…”
Section: Predictor Variablementioning
confidence: 99%
“…22 Chello et al recommended precise blood pressure management, which includes avoiding long-term hypotension and long-term use of vasoactive medications to prevent perioperative PI. 26 Huang et al listed the hypotension episodes and the use of vasoactive medications among risk factors associated with the postoperative PI. 27 This may be explained by the fact that hypotension leads to impaired peripheral tissue perfusion which increases susceptibility to PI in areas of the body exposed to prolonged pressure.…”
Section: Discussionmentioning
confidence: 99%